Analysis of The Impact of The Mobile Legends Game n Children's Social Skills - Septian Putra Pratama; Bambang Gatot Sugiarto; Dhani Agusni (STKIP Pasundan Press, 2026)
This study aims to examine the impact of the Mobile Legends game on the social skills of junior high school students. The research used a descriptive quantitative approach with a social skills questionnaire covering aspects such as cooperation, communication, and empathy. A total of 29 seventh-grade students were selected purposively from a population of 73 students at SMP PGRI 1 Cimahi. The findings revealed that Mobile Legends has both positive and negative effects on children's social skills. Positive effects include enhanced teamwork and verbal communication among players. However, negative effects were also observed, such as decreased direct interaction with peers, reduced emotional control, and lower academic motivation. Most students were categorized as having fairly good social skills, with a small portion achieving higher levels. These results indicate that Mobile Legends significantly influences children's social development, depending on their playing frequency and the presence of guidance and supervision from parents and teachers.